Analysis of Barriers to PoS application users in MSMEs based on Google play store review - Wildan Zulfikar Djunaedi; Adam Mukharil Bachtiar; Akhrarova Shoira Batirovna (Universitas Komputer Indonesia, 2026)
Transformation to digital through Point of Sale (POS) software can offer a lot of operational efficiency for MSMEs but the adoption is still not optimal because of the limitations of the users themselves. In this research, we will seek to explore, categorize, and prioritize the main operational challenges faced by MSME entrepreneurs using the Kasir Pintar app. Using the quantitative approach in text mining, the data collection process used a total of 10,000 user reviews from the Google Play Store on 13 July 2026. Filtering out low ratings (1 & 2) provided 421 reviews and after preprocessing (folding, cleaning, tokenizing, normalization, preserving stopwords for negation semantics, and Sastrawi stemming), we had 395 cases. Based on the results, the most frequent words or tokens include “tidak” (229 times), “daftar” (61), “data” (55), “masuk” (51), “akun” (50), and “barang” (45). The above complaints have been systematically synthesized to formulate a new barrier taxonomy consisting of four categories: technical and system barriers (failure of authentication and OTP), integration and data barriers (data loss and failure of receipt printer connection), customer service barriers (non-responsive helpdesk support) and commercial barriers (re-registration issues and price sensitivity). In practice, it emerges from this study that the instability of the software causes a vicious multiplier effect, forcing the merchants to rely on their inefficient manual record keeping during peak sales time, and losing customer trust and increasing application churn. In the context of PoS application development, these insights provide strategic priorities in the form of developing multi-channel OTP authentication (whatsapp and email) and offline first local synchronization to avoid data loss, along with SLA based customer support